Infecções agudas por vírus sincicial respiratório em crianças hospitalizadas por doenças do aparelho respiratório inferior - Salomão Junior, João Batista (2008)
Acute lower respiratory tract disease (ALRTD) accounts for high infantile mortality and morbidity rate worldwidely. Respiratory syncytial virus (RSV) is frequently found among pathogens. Objectives: The objectives were: 1) to evaluate the RSV frequency in children from 0 to 6 years hospitalized due to acute lower respiratory disease in São José do Rio Preto, SP; 2) to characterize the virus seasoning in this city and 3) to verify possible association among epidemiologic, clinical and diagnostic data with this viral agent. Casuistic and Method: From May 2004 to September 2005, 278 children aged from 0 to 6 years with ALRTD were studied. They have contracted the disease in the community, hospitalized in the children s ward, emergency room and Pediatric Intensive Care Unit of Hospital de Base, São José do Rio Preto. They were asymptomatic in a 7-day period before the beginning of the disease. Questionnaires were used for the children's characterization and their clinical presentation. Samples of nasopharyngeal secretion were collected to identify RSV, using reverse transcription polymerase chain reaction (RT-PCR). Results: The results showed that in the 290 hospitalizations of ALRTD, RSV was positive in 29.3%. ALRTD was more frequent in infants (average = 13.5 months) and male (57.6%). RSV was more frequent in bronchiolitis cases (64%). RSV+ infections were more frequent in the first year of life (35%). In RSV + infections, pneumonia frequency varied from 19.5 to 26.2% in the studied age groups; acute wheezing was observed in 31.8% of children aged over 2 years; bronchiolitis was registered in 62.5% of the children younger than 1 year; pneumonia with pleural effusion was noticed in 18.7% of the children aged over 2 years. Conclusions: The frequency of RSV in children from 0 to 6 years hospitalized due to ALRTD was 29.3% in São José do Rio Preto, SP. The ALRTD were more frequent between June and November 2004. In 2005, the hospitalizations occurred mainly starting from March decreasing in September. There was RSV prevalence in children younger than 2 years, male and with bronchiolitis. The RSV frequency in the hospitalizations was higher in 2004 than in 2005. In the RSV+ infections, the cases of pneumonia had similar occurrence in the studied age groups. There was reduction of the RSV frequency as age increases in the cases of pneumonia with pleural effusion and increase in the cases of acute wheezing; in bronchiolitis most of the RSV+ cases occurred in children younger than1 year. The clinical and radiological data obtained did not allow the proper identification of the infection by RSV. Laboratory examination by means of RT-PCR was necessary to identify it.